Determinação de compostos sulfurados em amostras de asfalto de petróleo empregando cromatografia líquida com detecção pulso-amperométrica - Schmidt, Patricia (2018)
Among the heteroatoms present in petroleum, sulfur stands out as being the most abundant. Henceforth it can be found on many quantities in oil derivate, such as Petroleum Asphalt Cement (CAP). The presence of organosulfur compounds on asphalt matrix is related to the matrix aging processes, making it brittle and reducing the useful life of the pavement. Even more some of these compounds can be used as pollution markers in environmental analysis, and geological markers. We can also tie the presence of such elements as an occupational health hazard, seeing as some of them have a known carcinogenic and mutagenic potential. In face of that, this research had the objective of developing and validate a high performance liquid chromatography method with pulsed amperometric detection (HPLC-PAD), which allow the determination of sulfur compounds in asphalt matrices. Using a gold electrode as a working electrode, a method with isocratic elution was developed that allows the determination of 11 organosulfur compounds. Two methodologies of sample preparation were studied in order to verify the presence of the organosulphur compounds in the crude sample, through a procedure of solid phase extraction (SPE) utilizing aminopropyl cartdriges, and in form of volatiles, through extraction using an extraction and collector device (DEC). In addition, a study of the amperometric detection of 22 compounds containing sulfur, including some in its oxidized form, was carried out in order to compare the reaction efficiency in a gold and carbon electrodes. The developed and validated chromatographic method present low detection limits, between 0,05 mg L-1 for dibutyldisulphite and 0,95 mg L-1 for 4-metyldibenzothiophene. The method was applied in the characterization of a crude sample of asphalt cement, allowing to determine the 3-phenylthiophene compound in form of volatiles, in the concentration of 0,160 mg kg-1.